Economic dynamics and general equilibrium time and uncertainty - Borglin Anders (Berlin Springer-Verlag, 2004)
This book focuses on the developments in the theory of incomplete markets and overlapping generations economies where income transfers over time or across states are restricted either by available assets or by the infeasibility of contracts with unborn ge
Keywords: Mathematical economics; Uncertainty(Economics)